Status of mercury accumulation in agricultural soil across China: Spatial distribution, temporal trend, influencing factor and risk assessment. (September 2018) - Zhou, Yuting; Aamir, Muhammad; Liu, Kai; Yang, Fangxing; Liu, Weiping
Abstract: Given its wide distribution in the natural environment and global transport potential, mercury (Hg) is regarded as a ubiquitous pollutant. In this study, we carried out nation-wide sampling campaigns across China to investigate the distribution of Hg in agricultural soils. Concentrations of Hg in the soils collected in 2011 and 2016 ranged from 0.04 to 0.69 and 0.06–0.78 mg kg −1, respectively. Based on the data from 2016, the reserve of Hg in the surface arable soils (0–20 cm) in China was 4.1 × 10 4 metric tons and Chinese cultivated soils accounted for 63.4–364 metric tons of Hg released to the global atmosphere. The soil Hg concentrations were significantly higher than the reference background level, highlighting the impacts of anthropogenic activities. The vertical distribution pattern showed a clear enrichment at the surface and a decrease with depth of the soils. Comparison of calculated geo-accumulation indexes among individual provinces showed that Northwest China had higher levels of Hg contamination than other regions of China, likely due to long-term energy related combustions in the area. Soil Hg level showed strong positive correlations with organic matter contents of soil, as well as the mean annual precipitation and temperature of the sampling locations. The non-carcinogenic human health risks of soil Hg were below the threshold level, but the general risk to the ecosystem was considerable. The increases in Hg accumulation from 2011 to 2016 at provincial level were found to relate to coal combustion, power generation and per capita GDP. This examination of energy consumption and socioeconomic drivers for China's soil Hg reserve increase is critical for direct Hg control by guiding policy-making and targets of technology development in era of rapid economic growth. Graphical abstract: Image 1 Highlights: Nation-wide mercury concentration, distributions, and potential risks in agricultural soils in China were determined. Temporal accumulation trend of soil Hg was identified and the increases were closely related to anthropogenic activities. Correlations between Hg and soil properties as well as meteorological parameters were estimated.